2017
DOI: 10.1002/mgg3.331
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of osteogenesis imperfecta in the Palestinian population: molecular screening of 49 affected families

Abstract: BackgroundOsteogenesis imperfecta (OI) is a heterogeneous hereditary connective tissue disorder clinically hallmarked by increased susceptibility to bone fractures.MethodsWe analyzed a cohort of 77 diagnosed OI patients from 49 unrelated Palestinian families. Next‐generation sequencing technology was used to screen a panel of known OI genes.ResultsIn 41 probands, we identified 28 different disease‐causing variants of 9 different known OI genes. Eleven of the variants are novel. Ten of the 28 variants are locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 65 publications
(107 reference statements)
0
16
1
1
Order By: Relevance
“…No biallelic mutations associated with recessive OI were observed in our study. This is totally different from the findings in a report by Essawi et al, which showed that 61% of individuals in their study were affected with autosomal recessive OI in a Palestinian population [22]. The prevalence of recessive OI may depend on geographical area, as recessive disorders can be more frequent where consanguinity is common.…”
Section: Discussioncontrasting
confidence: 96%
“…No biallelic mutations associated with recessive OI were observed in our study. This is totally different from the findings in a report by Essawi et al, which showed that 61% of individuals in their study were affected with autosomal recessive OI in a Palestinian population [22]. The prevalence of recessive OI may depend on geographical area, as recessive disorders can be more frequent where consanguinity is common.…”
Section: Discussioncontrasting
confidence: 96%
“…As an endoplasmic reticulum localization protein, FKBP65 binds to tropoelastin throughout the secretory process (32). Investigations into FKBP10 have primarily focused on pulmonary fibrosis and osteochondrosis; FKBP10 mutations has been linked to the onset of many diseases (33,34). As a connective tissue disease, Bruck syndrome is mainly characterized by the loss of endopeptide lysine hydroxylation at the molecular level, leading to the reduction of collagen pyrimidine cross-linking (35).…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, out of 337 OI patients in the UT OI biobank, less than 2% suffered from OI type V (five individuals). Interestingly, in a cohort of Palestinian OI patients, there were no carriers of the IFITM5 pathogenic variants, as well as among our Estonian OI population [40]. We do not have evidence to assume, that such differences might come from distinctions in the population genetics of different ethnic groups.…”
Section: Discussionmentioning
confidence: 78%